Women's Right to Land Between Collective and Individual Dimensions. Some Insights From Sub-Saharan Africa - Errico, Stefania (Frontiers in Sustainable Food Systems, 2021)
Women represent a large part of the 2.5 billion people who depend on lands managed through customary, community-based tenure systems and are especially reliant on commons for their lives and livelihoods. They have very often limited and unsecured access to land and natural resources and tend to be excluded from decisions concerning them. Far from representing a homogenous group, they face varying challenges that are the result of multiple and intersecting forms of discrimination, whereby gender dynamics intersect with other characteristics, such as age, disability, ethnic origin or socioeconomic status. Peasant and indigenous women, in many instances, face the compounded impact of the lack of recognition and violation of the collective rights of their communities, which is often the legacy of histories of colonization, conquest, dispossession and discrimination, and patriarchal norms, exacerbated by neoliberalism and the commodification of land and natural resources. The nexus between individual and collective rights is one of particular importance, but has received limited attention, including as regards the gendered effects of human rights violations of collective rights. In the present article, the nexus between collective and individual rights of peasant and indigenous women is illustrated by considering the experience surrounding the recognition and implementation of collective rights to land in Sub-Saharan Africa and the impact on women’s right to land. The article argues that peasant and indigenous women’s right to land is best protected through interventions aimed at guaranteeing both their collective and individual rights. There is a need to take into account and address simultaneously the barriers that indigenous and peasant women face with regard to their collective as well as their individual rights. These barriers include those ascribed to the discrimination and social, economic and political marginalisation suffered by their peoples and communities, as well as those related to the patriarchal power structures that prevail within and outside them. Addressing these barriers requires the respect, protection and fulfilment of both collective and individual human rights of women and a careful analysis of the interaction between these rights.